The Influence of Safety Management Practices on Safety Performance in Nurses of Emergency Installation on The Government Hospital of Surabaya - Khaulah Syahidah; Noeroel Widajati; Nurhayati Saridewi (Institute of Medico-legal Publications Pvt Ltd, 2022)
Introduction: Hospital is one of the high-risk workplaces in terms of safety and health. Nurses arethe most vulnerable health workers to work accidents because they have the most number in a hospitaland most often interact with patients. Safety performance is very important for the prevention of workaccidents. This research aimed to analyze the influence of safety management practices on safetyperformance in nurses of the emergency installation at X Hospital of Surabaya.Methods: This research was an observational research with the cross-sectional design. It was conductedin May to June 2019. The population in this study was 208 nurses and the sample obtained using asimple random sampling technique involving 68 nurses. In assessing safety management practices andsafety performance, the researcher used questionnaires, observation, and interviews.Results: The results presented that safety training which was a dimension of safety managementpractices affected on the safety performance with a p-value 0.000. Suggestions in this research, toimprove safety performance, management can conduct specific and periodic safety training, holdingsafety briefing and safety talk on a regular basis, and implementing a safety award by applying a systemof reward and punishment.Conclusion: Hospital management still needs to schedule a specific and periodic safety training fornurses. Furthermore, to improve safety performance, management can holding safety briefing andsafety talk on a regular